Engine Start-Up Torque Coordinated Control for Multimode Hybrid Electric Vehicle Equipped With a Two-Speed Dedicated Hybrid Transmission - Chongchong Li; Changyu Zhou; Jiangyong Xiong; Xinying Li; Yazhou Zhou (Shock and Vibration)
A multimode hybrid electric vehicle (HEV) equipped with a dedicated hybrid transmission (DHT) can be generally divided into pure electric mode with engine shutdown and hybrid mode with engine operation. Engine start-stop control is the key to achieving a transition between these two modes. To address the issues of engine start-up torque coordination control and torque interference, first, the start-up requirements of DHT-HEV engines in different driving scenarios are summarized, a multistage dynamic model for DHT-HEV engine start-up is established, and the key issues of engine start-up torque coordination control are analyzed. Second, an engine start-up torque coordinated control strategy with torque interference and parameter uncertainty is proposed, a robust model predictive controller (RMPC) is designed to adjust clutch pressure, a finite time disturbance observer (FTDO) is designed to obtain torque interference during the engine start-up process, and a sliding mode observer (SMO) is designed to obtain vehicle driving resistance torque. Finally, a simulation and hardware-in-the-loop (HIL) test are conducted to verify the performance of the relevant observers, torque coordination control, and interference compensation control during the engine start-up process.